Quadrate lobe: a reliable landmark for bile duct anatomy during laparoscopic cholecystectomy. Issue 7 (8th April 2016) - Rajkomar, Kheman; Bowman, Matthew; Rodgers, Michael; Koea, Jonathan B.
Abstract : Background: This investigation was undertaken to determine whether the shape of the inferior surface quadrate lobe (segment IV) can assist in defining a safe starting point for dissection during laparoscopic cholecystectomy. Methods: Patients undergoing laparoscopic cholecystectomy were prospectively audited. Intraoperative cholangiograms and photographs of the quadrate lobe were reviewed measuring the angle between the cystic duct and common bile duct and its relationship to quadrate shape. Results: The results of 56 patients were included. The shape of the inferior surface of the quadrate lobe was rectangular in 35, pyramidal in 13 and square in eight patients. The median cystic/bile duct angle was 43°, 37° and 26° for square, rectangular and pyramidal quadrate shapes, respectively. The angle for pyramidal‐shaped lobes was narrower than that for rectangular or square lobes ( P < 0.05). Regression analysis showed an inverse relationship between the shape ratio and the cystic/bile duct angle ( P = 0.015). Conclusion: This investigation confirms a relationship between the shape of the inferior surface of the quadrate lobe and the cystic/bile duct angle and suggests that the anatomy of the inferior surface of the quadrate lobe can be used to define an optimal starting point for dissection of the biliary cystic triangle.